Instalasi Jaringan Komputer Thin Client NComputing vSpace Tipe L130 pada Ruang Akademik SMAN 1 Bandar Baru - Sunardi, Rahmad (Yayasan Kawanad, 2024)
This study aims to implement a thin client network based on dumb terminal using NComputing vSpace Type L130 in the academic room of SMAN 1 Bandar Baru to enhance resource efficiency and computer system performance. The research was motivated by the high power consumption and maintenance complexity of conventional desktop systems in the school’s computer laboratory. The methodology includes definition, design, and verification stages, with testing focused on four parameters: CPU usage, memory consumption, network throughput, and power consumption. The implementation utilized a Lenovo X3650 M5 server running Microsoft Hyper-V Server 2012 R2 and five NComputing L300 units, connected via a 100 Mbps Ethernet network using the User Extension Protocol (UXP). Test results showed an average CPU usage of 35%, memory usage of 9 GB out of 16 GB, throughput of 85 Mbps, and power consumption of 5 watts per unit, achieving up to 97% energy savings compared to conventional desktops. The system supports administrative and web-based applications stably, reduces maintenance costs, and enables centralized management. This research offers an energy-efficient and scalable solution that can be replicated in other educational institutions with similar constraints.